The development of talent identification protocols for disability sport - Augustyn, N J. (2005)
Talent identification has been defined as the process by which children are measured on a number of physical and performance variables that are perceived to be a requisite for success within a given sport (Abbott & Collins, 2002:158). One important element in talent identification testing is the capacity to interpret scores. This requires the development of relevant norms for the populations groups who will be involved. The purpose of this study was to generate norms for the interpretation of scores earned by children with disabilities on a basic talent identification screening test battery. The study was focused only on children with intellectual impairments, children with hearing impairments and children with visual impairments. The Talent Search test battery as prescribed by DISSA (Disability Sport South Africa, 2002) found in their screening manual for basic sporting ability of persons with disabilities was used to assess subjects on performance variables. This included body height, sitting height, arm span, body mass, eye-hand coordination, sound localization and eye- hand coordination (for the those with VI), upper body power, leg power, agility, running speed and aerobic fitness (cardiovascular endurance). The group of 140 subjects included 49 children with intellectual impairments (N=27 males and N=22 females), 58 children with hearing impairments (N=35 males and N=23 females) and 33 children with a visual impairment of which 11 (N=7 males and N=4 females) needed to run with a guide and 22 (N=17 males and N=5 females) where independent runners. The descriptive data was processed to produce percentile tables. One problem area was found with testing the eye-hand coordination of children with intellectual impairment, where more than 50% of the children were not able to obtain a score at all. It was also found that some children with hearing impairments had slow running times for the agility run test item, which led to the conclusion that vestibular etiology must be identified prior to the interpretation of test scores.